2012
DOI: 10.5539/jgg.v4n1p203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Industrial Activities on the Structure and Floristic Pattern of Vegetation within the Calabar Port Authority, South-Southern Nigeria

Abstract: The paper evaluated the effects of industrial activities on the structure and floristic pattern of woody tree/shrub species in the Calabar Port Authority. Three plots of 0.16 ha were employed to collect vegetation parameters (structure and floristic) from vegetation adjoining highly impacted site (HIS) and of less impacted site (LIS). Shannon-Wiener's index showed that vegetation in the LIS was more diverse and heterogeneous than vegetation in the HIS with species diversity index of 2.29 and 2.26 respectively;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The result of the study revealed that plot A is the richest, having highest value of species richness when compared with other plots, meaning that plot A is less disturbed or impacted when compared with other plots. This is in agreement with Offiong et al (2011) who observed that vegetation in the less impacted site was richer, more diverse and heterogeneous than vegetation in impacted site. However, the general reduction in species richness observed in most of the plots is an indication that the area was recently disturbed and thus typical of secondary rain forest after disturbance.…”
Section: Discussionsupporting
confidence: 93%
“…The result of the study revealed that plot A is the richest, having highest value of species richness when compared with other plots, meaning that plot A is less disturbed or impacted when compared with other plots. This is in agreement with Offiong et al (2011) who observed that vegetation in the less impacted site was richer, more diverse and heterogeneous than vegetation in impacted site. However, the general reduction in species richness observed in most of the plots is an indication that the area was recently disturbed and thus typical of secondary rain forest after disturbance.…”
Section: Discussionsupporting
confidence: 93%
“…This corroborates the affirmation of Offiong et al (2012) that human activity is an important agent influencing plant species biodiversity.…”
Section: Resultssupporting
confidence: 89%
“…In addition, Offiong, Offiong and Ekpe (2014) focused on the socio-economic characteristics of property owners who comply with building regulations in Calabar, Nigeria. The study concluded that the socio-economic characteristics of property owners or residents, in particular income and educational status, determine the extent of adherence to building regulations in the study area.…”
Section: Literature Reviewmentioning
confidence: 99%